2015
DOI: 10.1039/c4ra10207j
|View full text |Cite
|
Sign up to set email alerts
|

Fe3O4@SiO2 nanoparticles as a high-performance Fenton-like catalyst in a neutral environment

Abstract: Fe3O4@SiO2 could be used as high-performance Fenton-like catalyst for dye decoloration in neutral environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…It was found that the removal efficiency of TC increases from 76.5 to 94% within 240 min reaction when the H 2 O 2 concentration increases from 20 mM to 80 mM. These findings are in good agreement with those of previously conducted studies 27,31 . It shows that TC removal is directly related to the concentration of HO• produced by the catalytic decomposition of H 2 O 2 .…”
Section: Effect Of H 2 O 2 Concentrationsupporting
confidence: 91%
“…It was found that the removal efficiency of TC increases from 76.5 to 94% within 240 min reaction when the H 2 O 2 concentration increases from 20 mM to 80 mM. These findings are in good agreement with those of previously conducted studies 27,31 . It shows that TC removal is directly related to the concentration of HO• produced by the catalytic decomposition of H 2 O 2 .…”
Section: Effect Of H 2 O 2 Concentrationsupporting
confidence: 91%
“…The kinetics of the FTCNC-H2O2-MB system was competitive with other systems using various nanocatalysts. For example, the Fe3O4@SiO2-H2O2-MB system had a k value of 0.020 min −1 [7]. The k values of the FePt-H2O2-MB system were in the range of 0.0033-0.023 min −1 at the pH value of 5.5 [20].…”
Section: Decoloration Of Mb In the Ftcnc-h 2 O 2 Fenton-like Systemmentioning
confidence: 90%
“…Typically, heterogeneous Fenton-like catalysts are microsized or nanosized and contain Fe or other metal elements, where the surface metal atoms catalyze the decomposition of H 2 O 2 . Many heterogeneous catalysts have been reported to catalyze the decomposition of H 2 O 2 for water treatment [6][7][8][9][10][11][12]. Both iron-containing and iron-free catalysts have been studied, and external energy supply (e.g., sonication [13,14], electricity [2] and light irradiation [9,[15][16][17]) is adopted in many cases to enhance the performance of heterogeneous catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…While the other three systems exhibited lower degradation efficiencies within the same time frame at 13.88 %, 32.38 % and 20.24 % for H 2 O 2 , Fe 3 O 4 @SiO 2 and Fe 3 O 4 ‐H 2 O 2 systems, respectively. The low degradation efficiencies observed in these systems is mainly caused by the near neutral pH and lack of external energy [12,36] . The effectiveness of the Fe 3 O 4 @SiO 2 nano‐catalysts in degradation of the malachite green dye was further confirmed by the evaluation of the degradation kinetics using the equation (2).…”
Section: Resultsmentioning
confidence: 90%
“…In this AOPs, highly reactive radicals are produced which then helps in oxidizing the organic pollutants [11] . Unlike the traditional activated sludge process, AOP's can handle a wide variety of pollutants and are now readily being employed in both laboratory and industrial scale [12] . Of the several possible routes for AOP, fenton reaction is the mostly widely deployed method which involves the decomposition of H 2 O 2 to hydroxyl and hydroperoxyl radicals in presence of Fe 2+ ions [13] .…”
Section: Introductionmentioning
confidence: 99%